Peningkatan Kompetensi Guru Mengoperasional Microsoft Excel untuk Pengolahan Nilai Hasil Belajar di MI Negeri 8 Gunungkidul dan MI Muhammadiyah Munggur Semanu - Karmanto (Jurnal Pendidikan Madrasah, 2020)
This research aims to find out the ability of teachers to process the value of students' learning results using microsoft excel. Microsoft excel implementation activities are conducted through group supervision in the form of training and mentoring. This research uses a method of action research and is carried out in two cycles. The results showed that training and mentoring activities can improve teachers' ability to operate Microsoft Excel. In cycle I, of the 18 teachers, 83.33% had poor criteria, 11.11% had enough criteria, and 5.56% had a good criteria with an average score of 62.35 in cycle I increasing to 83.70 in cycle II. Group supervision activities through training and mentoring can improve the ability of MI teachers in processing the value of learning results using Microsoft excel.